Evaluation of total phenolic content and antibacterial activity of aloe vera extract towards food-borne pathogens / Farah Aqilah Roslan - Roslan, Farah Aqilah (2015)
Aloe vera is known to have a number of therapeutic uses such as antibacterial and anti-inflammatory, with properties of good antioxidant sources. Recently, the increasing amount of multidrug resistance is quite worrisome‘ In conjunction with that, this research was conducted to determine total phenolic content and antibacterial activity of Aloe vera'extract against Staphylococcus aureus, Bacillus cereus, Escherichia coli and Salmonella typhimurium. By using 80% methanol ex‘raction method, the total phenolic content was measured in absorbance by Spectrophotometer UV-Vis while method of disk diffusion assay, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were used (0 determine antimicrobial activity of Aloe vera‘ From this study, it was shown that methanol extract of Aloe vera has total phenolic content of 5.20 mg GAE/g. Meanwhile, the experiment of antimicrobial activity of Aloe Vera extract had shown that both of yam positive bacteria, Staphylococcus aureus and Bacillus cereus were most sensitive towards Aloe vera extract, with MIC value measured at 62.5 mg/ml concentration of extract. Hence, it was concluded that Aloe vera posses good phenolic content and effectively act as antimicrobial agent against several pathogens.